(untitled) (Dissertare, 2019)
Leadership is an action that seeks to encourage and influence a group of individuals to mobilize the collective effort, in order to generate changes that allow reaching common goals. In the interest of addressing this phenomenon in the context of higher education institutions, the present paper focused on analyzing the professor´s fundamental role in university leadership, in order to overcome the challenges faced by the aforesaid educational institutions in the 21st century. This effort focused on discussing the teaching leadership styles applicable in the context of these organizations, taking into account the imperatives of the society of knowledge and the challenges posed by the different university functions. The methodology used is of a qualitative nature, based on the documentary review of the theoretical referents of the thematic field studied and on the application of critical hermeneutics as a method of analysis. As a final reflection, it emerges that in the university sphere, the professor’s leadership is particularly relevant, who in a continuous and dynamic process is able to lead a social group to reach a diversity of aims, which require the combination of different styles of leadership, with predominance of transformational leadership and with a strong ethical and distributive component, which with the help of technological tools allows to awaken participation, responsibility, sense of belonging and vocation of service, towards the pursuit of institutional purposes and collective benefit, honoring the commitment of the university to sustainable development.